The casebook of Victor Frankenstein : a novel - Ackroyd, Peter, 1949- (New York : Nan A. Talese, 2008)
As Victor Frankenstein begins conducting anatomical experiments to reanimate the dead, he at first uses corpses supplied by the coroner. But these specimens prove imperfect for Victor's purposes. Moving his makeshift laboratory to a deserted pottery factory in Limehouse, he makes contact with the Doomsday men--the resurrectionists--whose grisly methods put Frankenstein in great danger as he works feverishly to bring life to the terrifying creature that will bear his name for eternity.
Keywords: Frankenstein, Victor -- (Fictitious character) -- Fiction; Frankenstein's Monster -- (Fictitious character) -- Fiction; Shelley, Percy Bysshe, -- 1792-1822 -- Fiction; Shelley, Mary Wollstonecraft, -- 1797-1851 -- Fiction; Byron, George Gordon Byron, -- Baron, -- 1788-1824 -- Fiction; Polidori, John William, -- 1795-1821 -- Fiction; Scientists -- Fiction; Monsters -- Fiction; England -- Social life and customs -- 19th century -- Fiction; Psychological fiction